Multi-agency Cooperation in Protection and Rescue During Natural Disasters in Local Communities: A Case Study of the 2023 Floods - Tominc, Bernarda; Sotlar, Andrej (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The system of protection against natural and other disasters in Slovenia imposes considerable responsibility on municipalities. First and foremost, it concerns the organisation of civil protection and fire services, which are also the first to respond in the event of a natural or other disaster. In the event of larger, more complex disasters, municipalities cannot cope with their own capacities and resources alone but are assisted by regional and national protection and rescue forces. In the event of catastrophic floods in 2023, practically all key services had to operate in the most affected municipalities, from civil protection, companies and institutions and NGOs in the field of protection, rescue and assistance, police, Slovenian Armed Forces, and volunteers. Due to the different competencies, tasks, responsibilities, equipment, training, experience, and other differences between the aforementioned services, the organisation of rescue itself represented a special challenge, especially the coordination of so many, but at the same time so different agencies. The paper analyses the experiences of such multi-agency (co)operation in the event of a major natural disaster, and predicts further directions for research.